Refractive Accommodative Esotropia Treated by Asymmetric Refractive Accommodative Esotropia Correction - Li, Zhisheng; Li, Geng; Li, Xueqiang; Xue, Na; Sun, Lianjun; Zheng, Huifang; Lee, Lavonne Rayer; Fung, Diana Danlai (European Journal of Applied Sciences, 2021)
To compare deviation improvement in children with residual refractive accommodative esotropia after previous treatment with spectacles, part-time patching and visual training with asymmetric refractive accommodative esotropia correction vs. full hyperopic correction. 72 participants (F=34, mean age 5.81 years) with residual partially refractive accommodative esotropia, mean deviation without glasses was 18.33±5.61 prism dioptres (PD) at distance and 22.64±5.82 PD at near. Participants (mean baseline visual acuity 62.43±18.97 letters) were randomly assigned to treatment for 24-months with asymmetric refractive accommodative esotropia correction (n=36) or full hyperopic correction (n=36). Change in deviation, visual acuity, refraction and anisometropia from baseline to the 24-month assessed by a masked examiner until deviation resolved and visual acuity stabilized. At 24 months, mean deviation with glasses improved from baseline by 21 PD with asymmetric esotropia correction, by 7 PD with full hyperopic correction at near vision. Mean visual acuity was improved from baseline 72.08±16.62 letters to 108.06±2.47 letters; refraction was decreased from baseline 5.03±2.75 dioptres (D) to 2.49±1.39 D in refractive accommodative esotropia eye (EE) in asymmetric refractive accommodative esotropia correction group, Visual acuity difference between EE and dominated eye (DE) was reduced from baseline 3.22±3.39 to 0.25±0.44. Anisometropia was improved from the baseline 1.65±1.78 D to 0.14±0.14 D. Overall treatment outcome was not related to age, sex, or prior treatment history, but were related to better baseline deviation and visual acuity. Conclusion: Deviation and visual acuity were greater improvement with asymmetric esotropia correction than full hyperopic correction treatment at 24-month in children with residual refractive accommodative esotropia.